Generalised multistage modelling and tuning algorithm for class EF and class Φ inverters to eliminate iterative retuning - Nikiforidis,I; Arteaga,JM; Kwan,CH; Pucci,N; Yates,DC; Mitcheson,PD (IEEE Transactions on Power Electronics, 2022)
The additional complexity of Class EF and Class Φ inverters compared to their Class E counterparts, combined with parasitic effects becoming more prevalent as frequency and power levels increase, results in poor accuracy from traditional design methods, and usually additional iterations of manual retuning are required. In this work we propose an approach to simulating and tuning Class EF/Φ inverters, with various levels of accuracy depending on the level of knowledge of the system parasitics. Our method is comprised of a combination of analytic and numerical solving methods thus providing both insight on the progression of the algorithm and computational robustness. The aim of our algorithm formulation is to enable solutions to be found in an automated and fast way. The novelty in our work lies in the design method's concurrent capability to provide a generalised set of design inputs (e.g. DC to AC current gain, arbitrary drain voltage slope at turn on, Φ- branch resonance, etc.), inclusion of board and device non-linear parasitics, and the ability to design within the set of preferred component values. An example is shown for the design of a 50 W, 13.56 MHz inverter where the experimental setup approaches the theoretical efficiency of 97%. The algorithm changes the values of the components over 5% to 50% and improves the simulated waveform accuracy by 2 to 12 times compared to the design method based on first order approximations.